UPAYA PENGEMBANGAN GENOTIPE PADI LOKAL KABUPATEN KUANTAN SINGINGI - Chairil Ezward; Irfan Suliansyah; Nalwida Rozen; Indra Dwipa (Jurnal Sains Agro, 2019)
Rice (Oryza sativa. L) is the main food crop in Kuantan Singingi District, but stressful conditions such as drought often cause severe yield losses. The problem of drought never gets a solution, so that many farmers cultivate paddy rice but the planting technique is tugal. This review article aims to resolve this issue. Resolving issues in rainfed lowland rice cultivation, in drought conditions, then it can be done by integrating several relevant disciplines. But on the occasion of this review the authors focus on explaining one solution that can be done in developing or improving the local rice genotype characteristics of Kuantan Singingi Regency. The effort to obtain types of strains, cultivars, varieties (from a cross between local genotypes with superior varieties with certificates) that are able to adapt to drought conditions. In this writer the strain is obtained through a series of activities ranging from exploration, collection, identification characteristics (morphological characteristics and molecular / DNA characteristics), description of local genotypes, then hybridization or biotechnology (Transgene), and finally the selection process. Exploratory research and characteristics can use survey methods by purposive random sampling (purposive random sampling). Data is collected by identifying the characteristics of local rice plants directly to the field. The observations made were (1) geographical coordinates location, (2) morphological observations based on the rice descriptors manual according to the Ministry of Agriculture (2013) and IRRI (2007). The observed characters are qualitative and quantitative characters towards the character of grain and rice. Observation data were processed using Ms. software. Excel and (NTSYS-pc) version 2.02. The observations showed a diversity of morphological characters both quantitative and qualitative of grain and rice. Keywords : Local rice, Development, Kuantan Singingi Regency